An Evolutionary Perspective in Tourism: The Role of Socioeconomic Status on Extremeness Aversion in Travel Decision Making. (May 2022) - Kim, Jungkeun; Giroux, Marilyn; Park, Jooyoung; Lee, Jacob C.
The present research investigates a novel relationship between travelers' childhood socioeconomic status (SES) and travel decision-making. We theorize that travelers from lower childhood SES or resource-scarce/unpredictable environments are more likely to avoid extreme options in a choice set. Five studies consistently show that childhood SES is negatively associated with extremeness aversion in diverse travel choices. We also demonstrate that the general risk tendency mediates the relationship between childhood SES and extremeness aversion in travel decision making (studies 3A and 3B). Lastly, we reveal that childhood SES is more likely to predict extremeness aversion when a choice set involves a quality–price trade-off rather than a quality–quality trade-off (study 4). This research introduces evolutionary aspects to explain pervasive behavioral tendencies in the context of travel and tourism and offers new insights to practitioners.